2009 2nd International Workshop on Electron Devices and Semiconductor Technology 2009
DOI: 10.1109/edst.2009.5166118
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric polymer oxide semiconductor field effect transistor (POSFET) devices for touch sensing

Abstract: -This work presents the POSFET based touch sensing devices and their experimental evaluation. POSFET touch sensing devices presented here are primarily developed for the robotic applications. The design of these devices is inspired from human sense of touch. These devices are implemented by spin coating thin (~2.5 µm) piezoelectric polymer (PVDF-TrFE) film, directly on to the gate area of MOS transistor. The polymer film is processed in situ. The POSFET device represents an integral "sensotronic" unit comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…The change in sensor capacitance as a function of temperature (~ 7 pF/°C) for all three conditions studied is comparable with that of force (7.5 pF/N) for forces < 0.5 N. We therefore propose that this P(VDF-TrFE) tactile sensor could be explored for temperature sensing in addition to its current application for pressure/touch sensing [18]. Previously a p-n junction temperature diode was combined with POSFET to allow temperature monitoring [12].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The change in sensor capacitance as a function of temperature (~ 7 pF/°C) for all three conditions studied is comparable with that of force (7.5 pF/N) for forces < 0.5 N. We therefore propose that this P(VDF-TrFE) tactile sensor could be explored for temperature sensing in addition to its current application for pressure/touch sensing [18]. Previously a p-n junction temperature diode was combined with POSFET to allow temperature monitoring [12].…”
Section: Discussionmentioning
confidence: 68%
“…The sensor capacitance shows a logarithmic dependence on applied force over the investigated force range up to 9 N. Forces below 0.5 N show a much greater sensitivity (~ 7.5 pF/N) than forces between 3 and 9 N (~ 0.26 pF/N). High sensitivity at the lower force range is important, as the majority of manipulative tasks carried out by a humanoid robot during day to day activities are in the region of < 1 N force [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The periodic time of our dynamic stress is 1ms. Therefore a proper assumption can be suggested that there is negligible delay between input force and output voltage phase 47 . Experimentally, the stress can be realized by bending the substrate periodically 26 .…”
Section: Pn Junction Mos 2 Nanoribbon Based Devicementioning
confidence: 99%
“…To date, several types of pressure sensors, such as a resistive sensor with a metallic-particles-dispersed insulator [2], piezoelectric sensors [3,4], a strain gage sensor [5], and a selfcapacitive pressure sensor with a deformable insulator [6], have been developed. The resistive pressure sensor has a limitation in dynamic range and in the number of multi-point detections.…”
Section: Introductionmentioning
confidence: 99%